2018
DOI: 10.1111/bjd.17209
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia areata: a review of disease pathogenesis

Abstract: Summary Alopecia areata is a disease that causes hair loss, although it does not always look the same and its course is unpredictable. It typically presents as small spots of reversible hair loss on the beard or scalp that can easily be treated. It can also result in total scalp baldness (called alopecia totalis) with devastating psychological impacts for some patients, inadequate treatment options, and frequent relapses. This article is a narrative review of the main events that cause alopecia areata, conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
107
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(110 citation statements)
references
References 0 publications
1
107
0
2
Order By: Relevance
“…In this issue of the BJD, Rajabi et al present a comprehensive review of recently proposed pathogenic mechanisms of AA. 3 In 1993, Paus et al first suggested the collapse of hair follicle (HF) immune privilege (IP) in AA. 4 Past observations suggested that HFs, especially the proximal portion including the bulb, enjoy IP that is enabled by several mechanisms: the absence or low-expression of major histocompatibility complex (MHC) class Ι and its pathway-related genes; the downregulation of interferon regulatory factor-1; the upregulation of immunosuppressive or proapoptotic molecules (IP guardians) such as transforming growth factor (TGF)-b, a-melanocyte-stimulating hormone (MSH), indoleamine-2,3-dioxygenase (IDO), protein red encoded by the IK gene (red/IK), interleukin (IL)-10, calcitonin gene-related peptide (CGRP), insulin-like growth factor (IGF-1), somatostatin, Fas ligand and programmed death-ligand 1 (PD-L1); the absence of MHC class ΙΙ + cells or Langerhans cells; the sparse distribution of T cell and natural killer (NK) cells; NK cell prevention machinery [low MHC class I polypeptide-related sequence A (MICA) expression, production of macrophage migration inhibitory factor (MIF), downregulation of NKG2D and upregulation of killer cell Ig-like receptor (KIR) on local NK cells]; the absence of lymphatics and the presence of relatively rich extracellular matrix, etc.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In this issue of the BJD, Rajabi et al present a comprehensive review of recently proposed pathogenic mechanisms of AA. 3 In 1993, Paus et al first suggested the collapse of hair follicle (HF) immune privilege (IP) in AA. 4 Past observations suggested that HFs, especially the proximal portion including the bulb, enjoy IP that is enabled by several mechanisms: the absence or low-expression of major histocompatibility complex (MHC) class Ι and its pathway-related genes; the downregulation of interferon regulatory factor-1; the upregulation of immunosuppressive or proapoptotic molecules (IP guardians) such as transforming growth factor (TGF)-b, a-melanocyte-stimulating hormone (MSH), indoleamine-2,3-dioxygenase (IDO), protein red encoded by the IK gene (red/IK), interleukin (IL)-10, calcitonin gene-related peptide (CGRP), insulin-like growth factor (IGF-1), somatostatin, Fas ligand and programmed death-ligand 1 (PD-L1); the absence of MHC class ΙΙ + cells or Langerhans cells; the sparse distribution of T cell and natural killer (NK) cells; NK cell prevention machinery [low MHC class I polypeptide-related sequence A (MICA) expression, production of macrophage migration inhibitory factor (MIF), downregulation of NKG2D and upregulation of killer cell Ig-like receptor (KIR) on local NK cells]; the absence of lymphatics and the presence of relatively rich extracellular matrix, etc.…”
mentioning
confidence: 99%
“…The uniqueness of the work by Rajabi et al lies in the way that the authors distinguish and discuss two individual scenarios for initial triggering of IP collapse. 3 One theory centres on environmental stress (e.g. reactive oxygen species) locally promoting MICA expression that activates the innate immune system via NKG2D + NK cells, which leads to subsequent interferon production and MHC class Ι upregulation to break HF-IP.…”
mentioning
confidence: 99%
See 3 more Smart Citations